Construcción experimental de un sistema transformable tensado plegable (2016)
The objective of this research is to develop an experimental model to study the characteristics of retractable systems. The experimental model involved the construction of a 4 limbs retractable umbrella. The experimental model by adding 8 members, in order to maintain better structural balance is then improved. The design model is supported by the European code EHE08, but was redesigned with LRFD code to have a diameter according to local requirements. In addition, the model helped form constructive concepts of movement of the folding systems umbrella-shaped, which resulted in a retractable folding system, which is bent on building a node to join two elements creating a structural system. This work was concluded that the transformable systems can help improve the design of flexible structural systems.